Case Report: Successful management of high-volume paclitaxel extravasation with hyaluronidase and dry warm compresses - Dudík, Boris; Kunderlík, Maroš; Mriňáková, Bela; Lukáčová, Zuzana; Ušáková, Vanda; Klimas, Ján (Frontiers in Oncology, 2025)
BackgroundPaclitaxel is a widely used chemotherapeutic agent with known vesicant properties. Extravasation is rare, but it can result in significant local tissue injury. There is no consensus on the optimal management strategy, and recommendations differ significantly.Case presentationWe report the case of a 63-year-old woman with metastatic cervical cancer who experienced a large-volume paclitaxel extravasation during a peripheral infusion. Management involved immediate subcutaneous administration of hyaluronidase around the affected area, followed by repeated applications of dry warm compresses. The patient reported only mild discomfort during treatment, and the local cutaneous symptoms resolved within days. Despite effective local management, the patient developed persistent paresthesia in the extravasated limb, later diagnosed as sensory neuropathy affecting the ulnar nerve. This was accompanied by lower limb neuropathy, likely related to the systemic paclitaxel exposure. Paclitaxel was discontinued, and the patient continued palliative treatment with carboplatin monotherapy.ConclusionBased on our literature search, this appears to be the first documented case of high-volume paclitaxel extravasation successfully managed with both hyaluronidase and dry warmth. The intervention proved to be effective in preventing severe local tissue injury, although it did not mitigate neurotoxic effects. Further research is needed to establish standardized management protocols.